2013
DOI: 10.1371/journal.pone.0077794
|View full text |Cite
|
Sign up to set email alerts
|

Osthole Mitigates Progressive IgA Nephropathy by Inhibiting Reactive Oxygen Species Generation and NF-κB/NLRP3 Pathway

Abstract: Renal reactive oxygen species (ROS) and mononuclear leukocyte infiltration are involved in the progressive stage (exacerbation) of IgA nephropathy (IgAN), which is characterized by glomerular proliferation and renal inflammation. The identification of the mechanism responsible for this critical stage of IgAN and the development of a therapeutic strategy remain a challenge. Osthole is a pure compound isolated from Cnidiummonnieri (L.) Cusson seeds, which are used as a traditional Chinese medicine, and is anti-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 62 publications
2
67
0
Order By: Relevance
“…It has been reported that NF-κB activation is associated with NLRP3 inflammasome formation [81,87,88]; however, the crosstalk between NF-κB pathway and NLRP3 inflammasome is still obscure. According to previous studies, we suppose that the involved mechanism may be partial due to NF-κB activation increasing the gene transcription of NLRP3, which contributes to NLRP3 inflammasome formation [89,90].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that NF-κB activation is associated with NLRP3 inflammasome formation [81,87,88]; however, the crosstalk between NF-κB pathway and NLRP3 inflammasome is still obscure. According to previous studies, we suppose that the involved mechanism may be partial due to NF-κB activation increasing the gene transcription of NLRP3, which contributes to NLRP3 inflammasome formation [89,90].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that imperatorin directly activated Ca 2+ flux in human neutrophils and transfected FPR1 HL-60 cells and that bergapten did not inhibit Ca 2+ mobilization in f MLF-stimulated human neutrophils and FPR1 HL-60 cells (Table 2), thus excluding these compounds as possible FPR1 antagonists. It should be noted that osthol is a known plant-derived compound with anti-inflammatory activity and a broad spectrum of molecular targets [109, 110]. Osthol had a weak inhibitory effect on f MLF-induced HNE release [94].…”
Section: Small-molecule Non-peptide Fpr1 Antagonists and Their Synmentioning
confidence: 99%
“…Silva et al demonstrated that the over-expression of NF-κB was correlated with poor prognosis in patients with IgAN [30]. Activation of NF-κB is also crucial in the progression of the renal pathology of IgAN [31]. In addition, the DNA sequences containing the rs2430561 and rs1861494 are the specific binding sites for the NF-κB transcription factor.…”
Section: Discussionmentioning
confidence: 99%